Crowdsourcing for dummies - Grier, David Alan, 1955 February 14- (Wiley, 2013)
Give your business the edge with crowd-power! Crowdsourcing is an innovative way of outsourcing tasks, problems or requests to a group or community online. There are lots of ways business can use crowdsourcing to their advantage: be it crowdsourcing product ideas and development, design tasks, market research, testing, capturing or analyzing data, and even raising funds. It offers access to a wide pool of talent and ideas, and is an exciting way to engage the public with your business. Crowdsourcing For Dummies is your plain-English guide to making crowdsourcing, crowdfun.